King Al : how Sharpton took the throne - Howell, Ron (New York : Empire State Editions, an imprint of Fordham University Press, 2021)
"Through the 1980s, the mainstream press portrayed Reverend Al Sharpton as a buffoon, a fake minister, a hustler, an opportunist, a demagogue, a race traitor, and an anti-Semite. Today, Sharpton occupies a throne that would have shocked the white newspaper reporters who covered him forty years ago. A mesmerizing story of astounding transformation and survival, King Al follows Reverend Sharpton's life trajectory, from his early life as a boy preacher to his present moment as the most popular Black American activist/minister/cable news host. In the 1980s, Rev. Al created controversies that would have doomed a lesser man to the dustbin of history. Among those controversies were his work with the FBI, as the agency attempted to locate Black Liberation Army leader Assata Shakur; and his involvement in the 1987 Tawana Brawley episode. Regarding the Brawley matter, a white prosecutor sued Sharpton, successfully, for falsely accusing him of having raped the then-15-year-old Brawley. It was the white press, in its glory days, that created the podium from which Sharpton became both famous and infamous. Those reporters would joke that the most dangerous place in New York was between Al Sharpton and a television camera. But it was those reporters who made Sharpton the media figure he is today. Today, as host of MSNBC's PoliticsNation news program, Sharpton has more news viewers than those reporters ever had as readers. Reverend Al's rise to respectability is a testament to an endurance and boldness steeped in Black American history. Born in Brooklyn, to parents from the old slave-holding South, he transformed himself into one the most respected and politically influential Blacks in the United States. In his in-depth coverage, author Ron Howell tells the stories of Sharpton's ascendance to the throne. He tells us about the glory years of American newspapers, when Sharpton began his rise. And he tells us about the politicians who intersected with Sharpton as he climbed the ladder. King Al is an engaging read about the late twentieth century history of New York City politics and race relations, as well as about the remarkable staying power of the colorful, politically skillful, and enigmatic Sharpton"--
11 Confessions of a Hack (i.e., Old- time Tabloid Reporter) -- Acknowledgments -- Tools That Made the Book -- Index
Online resource; title from digital title page (viewed on August 20, 2021).
Includes bibliographical references and index.
In English.
JSTOR
Keywords: Sharpton, Al; Sharpton, Al; African American civil rights workers -- Biography; African American clergy -- New York (State) -- New York -- Biography; African American politicians -- New York (State) -- New York -- Biography; African American television journalists -- Biography; Clergy -- New York (State) -- New York -- Biography; Politicians -- New York (State) -- New York -- Biography; New York (N.Y.) -- Biography; Défenseurs des droits de l'homme noirs américains -- Biographies; Clergé noir américain -- New York (État) -- New York -- Biographies; Politiciens noirs américains -- New York (État) -- New York -- Biographies; Journalistes de télévision noirs américains -- Biographies; Clergé -- New York (État) -- New York -- Biographies; Politiciens -- New York (État) -- New York -- Biographies; HISTORY / United States / State & Local / Middle Atlantic (DC, DE, MD, NJ, NY, PA).; African American civil rights workers; African American clergy; African American politicians; African American television journalists; Clergy; Politicians; New York (State) -- New York; Blacks; Brooklyn; Journalism; PoliticsNation; Sharpton; Biographies